The Habituation of Religious-Based Programs to Strengthen Religious Character in Early Childhood at Al Furqon Kindergarten, Sindangbarang Village, Kuningan Regency - Shobicha, Shobicha (Al-Banat: Journal of Early Childhood Islamic Education, 2025)
Background: Early childhood is a critical period for character development, as cognitive, emotional, and moral foundations are formed during this stage. Religious character education is particularly important in early childhood institutions, yet empirical research on structured religion-based habituation programs remains limited, particularly in Indonesian contexts.Objective: This study investigates how religious habituation programs strengthen religious character among early childhood learners at TK Al Furqon, Kuningan Regency, West Java. It identifies habituation program types, examines developmental phases, and analyzes outcomes related to religious competence and prosocial behavior within institutional, family, community, and cultural systems.Method: A qualitative case study was conducted during the 2024–2025 academic year. Data were collected through participant observation, in-depth interviews, document analysis, and focus group discussions involving teachers, administrators, parents, and students. Data triangulation ensured credibility and validity.Findings and Implications: Five religious habituation programs were identified: Qur'anic literacy and memorization, ritualized prayer habituation, moral character development, tawhid and Islamic knowledge instruction, and spiritual community ritual integration. Habituation progressed through three phases: external compliance, transitional internalization, and consolidating automaticity. Results showed that 87% of learners achieved Qur'anic recitation proficiency, 78% consistently participated in prayer, and 72% of parents reported increased prosocial behavior. A multidimensional habituation model integrating behavioral repetition, emotional engagement, peer modeling, ecological alignment, identity integration, and meaning-making was developed.Conclusion: Structured religious habituation programs significantly strengthen religious character development in early childhood when supported by aligned institutional, family, community, and cultural systems. The findings provide evidence-based guidance for educators and policymakers in designing effective religion-based habituation programs in early childhood education.